Interventions for preventing and treating kidney disease in Henoch-Schönlein Purpura (HSP) - Wattana Chartapisak (2018)
Background: To determine the benefits and harms of therapies used to prevent or treat kidney disease in Henoch-Schönlein Purpura (HSP). Objectives: To evaluate the benefits and harms of different agents (used singularly or in combination) compared with placebo or no treatment or another agent for the prevention or treatment of kidney disease in patients with HSP. Search strategy: Randomised controlled trials (RCTs) and quasi-RCTs were identified from the Cochrane Renal Group's specialised register, the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE and EMBASE using optimally sensitive search strategies combined with search terms for HSP. Selection criteria: RCTs comparing any intervention used to prevent or treat kidney disease in HSP compared with placebo, no treatment or other agents were included. Data collection and analysis: Three authors independently assessed trial quality and extracted data from each study. Statistical analyses were performed using the random effects model and the results were expressed as risk ratio (RR) for dichotomous outcomes and mean difference (MD) for continuous outcomes with 95% confidence intervals (CI). Main results: Ten studies (1230 children) were identified. There was no significant difference in the risk of persistent kidney disease at six months (3 studies, 379 children: RR 0.51, 95% CI 0.24 to 1.11) and 12 months (3 studies, 498 children: RR 1.02, 95% CI 0.40 to 2.62) in children given prednisone for 14 to 28 days at presentation of HSP compared with placebo or supportive treatment. In children with severe kidney disease, there was no significant difference in the risk of persistent kidney disease with cyclophosphamide compared with supportive treatment (1 study, 56 children: RR 1.07, 95% CI 0.65 to 1.78) and with cyclosporin compared with methylprednisolone (1 study, 19 children: RR 0.39, 95% CI 0.14 to 1.06). Authors' conclusions: Data from RCTs for any intervention used in improve kidney outcomes in children with HSP are very sparse except for short-term prednisone. There was no evidence of benefit of prednisone in preventing serious long-term kidney disease in HSP. Copyright © 2009 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd.